2009
DOI: 10.1002/cjce.20167
|View full text |Cite
|
Sign up to set email alerts
|

Clusters identification and characterization in a gas–solid fluidized bed by the wavelet analysis

Abstract: The local solid flow structure of the bubbling fluidized bed of sand particles was investigated in order to identify and characterize the clusters. Extensive experiments were carried out using an optical fibre probe, measuring the velocity and the diameter of clusters. Under all operating conditions, ascending and descending clusters co-existed at all measurement locations. The locus of the inversion point at which the directions of cluster motion changed was determined. The velocity of the ascending clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The existence of clusters in the riser has been experimentally observed by several researchers . When clusters are formed, two phases can be distinguished in each zone, encompassing a particle‐free gas phase and a particle‐rich cluster phase, similar to the particle‐free bubble phase and the particle‐rich emulsion phase in the traditional two‐phase model for the bubbling regime.…”
Section: Model Developmentmentioning
confidence: 95%
“…The existence of clusters in the riser has been experimentally observed by several researchers . When clusters are formed, two phases can be distinguished in each zone, encompassing a particle‐free gas phase and a particle‐rich cluster phase, similar to the particle‐free bubble phase and the particle‐rich emulsion phase in the traditional two‐phase model for the bubbling regime.…”
Section: Model Developmentmentioning
confidence: 95%
“…The second order Daubechies wavelet (DB2) was chosen as the mother wavelet for analysis of the vibration signals since it resulted in the minimum residual for a given order and scale among other mother wavelets tested [31,32]. The Shannon entropy was used to obtain the required level of decomposition and it was found that 9 levels of decomposition are enough for extracting all required information from the signal [33].…”
Section: Wavelet Decompositionmentioning
confidence: 99%
“…Various techniques including pressure/differential pressure, electrostatic, optical fibers have been developed to analyze fluctuation signals and identify flow regimes or characterize the hydrodynamics in gas‐solid flows. However, due to the complex nature of gas‐solid two phase flow systems and various origins of the signals, valuable and meaningful information is very hard to obtain .…”
Section: Introductionmentioning
confidence: 99%
“…They further pointed out that multiscale resolution analysis method is a powerful tool to detect multiscale flow structures in gas‐solid flow such as bubbles, clusters, agglomerates and so on. Wavelet analysis method is often used to decompose the original fluctuation signals into different scales based on the frequency of each scale signals . Some researchers have divided the decomposed signals into three scales, namely, microscale, mesoscale, and macroscale signals.…”
Section: Introductionmentioning
confidence: 99%